ENVIRONMENTAL IMPACT RESULTING FROM THE OPERATION OF HIGHWAY ENGINEERING WORKS IN SECTIONS OF THE ROAD-AXIS THERMOPYLES - NAFPACTOS - Μερτζάνης Α.; Παπαδόπουλος Α. (Bulletin of the Geological Society of Greece, 2004)
The object of this work is the environmental impact and especially the changes in the natural environment (with special emphasis in the geomorphological structure and the water resources) as a result of road works in places of lateral crossing of valley forms and of the hydrographie network. In order to evaluate these changes, we initially record the existing situation of the natural environment in selected parts of the mountainous part of the national road axis Thermopyles-Nafpaktos which are seen in the area of Skamnos-Bralos; we record the dynamic characteristics of the surface and underground waters as well as the erosion, rupture, movement of soil masses; then we note the changes in the natural environment up to now and especially in its geomorphological characteristics and in the water resources from the construction and operation of the project.